DETERMINASI YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KOTA BATAM - Banjarnahor, Haposan; Poniman, Poniman (LPPM Universitas Putera Batam, 2025)
Taxpayer Compliance as a Taxable Object is Crucial in Enhancing Tax Revenue This is particularly significant at the Primary Tax Office of South Batam City, an industrial region. This study aims to analyze the influence of tax comprehension, tax socialization, and tax services on taxpayer compliance.Testing Criteria The assessment uses the following criteria:Cronbach’s alpha value < 0.6 Poor reliability Cronbach’s alpha value 0.6 - 0.79 Acceptable reliability Cronbach’s alpha value ≥ 0.8 Good reliability Regression Analysis Results Variable X1 (Tax Comprehension) Positive regression coefficient (b = 0.150). Interpretation: A 1-point increase in X1 leads to a 0.150 increase in Y (taxpayer compliance). Variable X2 (Tax Socialization) Positive regression coefficient (b = 0.064).Interpretation: A 1-point increase in X2 leads to a 0.064 increase in Y. Variable X3 (Tax Services): Negative regression coefficient (b = -0.001). Interpretation: A 1-point increase in X3 results in a 0.001 decrease in Y. F-Test and Significance Analysis Calculated F-value (1.313) < F-table (3.939) Significance value (0.275) > 0.05 Conclusion: Variables X1, X2, and X3 do not simultaneously affect Y (taxpayer compliance